4+3y/6y-2=-3/5

Simple and best practice solution for 4+3y/6y-2=-3/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3y/6y-2=-3/5 equation:



4+3y/6y-2=-3/5
We move all terms to the left:
4+3y/6y-2-(-3/5)=0
Domain of the equation: 6y!=0
y!=0/6
y!=0
y∈R
We add all the numbers together, and all the variables
3y/6y+2-(-3/5)=0
We get rid of parentheses
3y/6y+2+3/5=0
We calculate fractions
15y/30y+18y/30y+2=0
We multiply all the terms by the denominator
15y+18y+2*30y=0
We add all the numbers together, and all the variables
33y+2*30y=0
Wy multiply elements
33y+60y=0
We add all the numbers together, and all the variables
93y=0
y=0/93
y=0
Równanie nie ma rozwiązania

See similar equations:

| (〖4D〗^4-〖8D〗^3〖-7D〗^2+11D+6)y=0 | | -7=7y+28 | | 4x-6=5(x-7) | | 144/4=n/6 | | (3x+5)/(4x+6)=5/4 | | (2x-1)-5=4x | | x^2+6x+3=-5 | | (6-2x)=-23 | | n^2+6n+3=-5 | | (6-2x)=23 | | 2x/3=4x | | 2.5/5=n/3 | | 5p+16=6 | | (2-3x)-1=0 | | 6(y-2)-3(y+3)-5(y+3)=0 | | 2x+38=3x-26 | | (x-7)+(x+1)=0 | | (-6-5x)=-61 | | (x+3)-(x-2)=4 | | 8+11n=14n–7 | | (x*61)*3.6=43.92 | | x/183=0.24 | | (-6-5x)=61 | | (7x+4)/2x=8 | | (5x)3=30 | | 16=4(z-5) | | 3(t-4)+8=14 | | 3t-4+8=14 | | 6=5u-u^ | | b/8+8=15 | | 7-5t=-6t | | X^2+36x+960=0 |

Equations solver categories